SCIENTIFIC, PHILOSOPHICAL AND PSYCHOLOGICAL INTERPRETATION OF THE PROBLEM OF CONSCIOUSNESS (Scientific journal of the Fergana State University, 2024)
The merits of the outstanding sciences I.P.Pavlov, I.M.Sechenov and Zigmund Freud, their teachings in the psychoanalysis and modern scientific philosophical and psychological conceptions of consciousness are noticed in the article on the problems of genesis u essence of consciousness and scientific justification of this phenaomenon.